Isothermal Drying Process and its Effect on Compressive Strength of Concrete in Multiscale - Xiangqin Du; Zongli Li; Taotao Tong; Bo Li; Hengjie Liu (Applied Sciences, 2019)
Drying could change the microstructure of cement-based materials and inevitably affect their mechanical properties. The isothermal drying process of concrete at three scales and its effect on compressive behavior and microstructure were investigated. The deformations of cement paste, mortar, and concrete in the drying process all exhibit the characteristics of expansion first and then shrinkage. The porosity and average pore diameter increase after drying, which is mainly attributed to the increase of pores less than 100 nm diameter for paste and to the pores within 100~1000 nm for mortar. Drying makes paste denser, while the bonding between paste and aggregate is weakened. Microstructural studies indicate that the increase in compressive strength of concrete caused by isothermal drying is the competition result between the strengthening effect and the weakening effect, and is related to the paste content.